1981
DOI: 10.1111/j.1471-4159.1981.tb04658.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic and Imprinting‐Induced Changes in Chick Brain Protein Metabolism and Muscarinic Receptor Binding Activity

Abstract: Over the 20-min period following exposure of young chicks to a flashing light as an imprinting stimulus there is an increased incorporation of [14C]leucine into an acidic (tubulin-enriched) protein fraction of the anterior dorsal forebrain in birds which have learnt the characteristics of the stimulus as compared with, either birds which have been exposed to an imprinting stimulus but learn poorly, or chicks kept in the dark. This brain region has been implicated in several studies as the locus for a number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The dysfunction of GABAergic and cholinergic neuronal systems plays an important role in the CXM-induced memory impairment of the passive avoidance task, since GABA agonists and acetylcholine (ACh) esterase inhibitors attenuate CXM-induced amnesia . Furthermore, there is much evidence that 3,-aminobutyric acid (GABA) play a role in the regulation of brain protein synthesis (Tapia et al, 1967;Sandoval et al, 1976), and that the cholinergic neuronal system is involved in the formation of memory (Rose etal., 1980;Longstaff and Rose, 1981;Sershen etal., 1982).…”
Section: Introductionmentioning
confidence: 95%
“…The dysfunction of GABAergic and cholinergic neuronal systems plays an important role in the CXM-induced memory impairment of the passive avoidance task, since GABA agonists and acetylcholine (ACh) esterase inhibitors attenuate CXM-induced amnesia . Furthermore, there is much evidence that 3,-aminobutyric acid (GABA) play a role in the regulation of brain protein synthesis (Tapia et al, 1967;Sandoval et al, 1976), and that the cholinergic neuronal system is involved in the formation of memory (Rose etal., 1980;Longstaff and Rose, 1981;Sershen etal., 1982).…”
Section: Introductionmentioning
confidence: 95%
“…In addition to describing a relationship between tubulin content and light conditions, Rose et al studied cerebral tubulin in relation to various behavioral paradigms in the chick. Colchicine binding activity was elevated in the anterior dorsal forebrain after passive avoidance learning (Mileusnic et al, 1980) but not after imprinting toward a flashing light or training in a two-way discrimination task (Longstaff and Rose, 1981).…”
mentioning
confidence: 92%
“…Other investigators [ 12,29,42] have also suggested the involvement of cholinergic synapses in the forebrain roof of chicks in the development of imprinting behavior, based on their findings that the activities of ChAT, AChE, and QNBbinding sites are elevated after the establishment of imprinting behavior.…”
Section: Intervention Studiesmentioning
confidence: 99%